Survei minat belajar siswa dalam mengikuti proses pembelajaran pendidikan jasmani, olahraga dan kesehatan SDN13 Tappong - Jaya Pangewangan, Much Amram; Ahmad, Ahmad; Nur, Suaib (Universitas Hamzanwadi, 2025)
This study aims to determine students' interest in learning in the learning process of physical education, sports and health at SDN 13 Tappong. The type of research used is descriptive quantitative with a survey approach. The population studied included all fifth grade students of SDN 13 Tappong, totaling 37 students. In this study, the entire population was used as a sample. The instrument used to collect data was a questionnaire, and data analysis was carried out using descriptive statistics techniques. Data analysis techniques were carried out using descriptive statistics through the SPSS program. The results showed that students' interest in learning Physical Education, Sports, and Health at SDN 13 Tappong was classified as high, with the highest frequency in the high category, namely 18 students or 48.64%. Meanwhile, the interest of students in the Very High category was recorded as 1 student (2.70%), the High category 18 students (48.64%), the Low category 14 students (37.83%), and the Very Low category there were 4 students (10.81%). In conclusion, students at SDN 13 Tappong mostly have a very high interest in learning in PJOK subjects. This interest is supported by student-centered teaching methods, teacher motivation, and a positive learning atmosphere.